Anatomy of Conflict - Maeshiba, Naoko (Performance Matters, 2024)
This essay explores physicality in the context of intercultural theatre and the conflicts, challenges, and questions that arise in bringing my Japanese self into the Western classroom. My inquiry revolves around the internal process of rethinking the physicality of actors through various lenses: space and body, emotion and body, logic vs. ambiguity, and Western horizontality vs. Japanese verticality. Special attention is given to the relationship between body and space, with reference to the work of a Japanese director and playwright Ōta Shōgo. Through an excavation of my roots and reflections on my past experiences, juxtaposed with discoveries in my current classroom, the essay tracks a gradual shift in my soma (body) as I entangle my Japanese/Western construct, move toward a reintegration of the two, and embrace the question of whether a universal approach to potentiality in performance is possible.